Treatment and Survival Outcomes in Rhino-Orbital Mucormycosis with and without Orbital Exenteration: A Retrospective Case Series and Literature Review - Boqaaiya S; Cohen Y; Beiruti Wiegler K; Chassid O (International Medical Case Reports Journal, 2025)
Shadi Boqaaiya,1,* Yuval Cohen,1,2,* Karine Beiruti Wiegler,3 Otzem Chassid1,2 1Ziv Medical Center, Department of Ophthalmology, Safed, 1311001, Israel; 2Azrieli Faculty of Medicine, Bar-Ilan University, Safed, 1311502, Israel; 3Research Wing, Ziv Medical Centre, Safed, 1311001, Israel*These authors contributed equally to this workCorrespondence: Shadi Boqaaiya, Department of Ophthalmology, Ziv Medical Center, Harambam Street 1, Safed, 1311001, Israel, Tel +972 532334355, Email shadybbd@hotmail.comAbstract: Rhino-orbital mucormycosis (ROM) is a life-threatening, fungal infection, primarily affecting immunocompromised patients. The role of orbital exenteration in treatment remains debated, especially regarding its impact on survival outcomes. This case series presents two patients from our Ophthalmology department and compares them with eight cases from the literature, focusing on treatment outcomes and survival rates. We specifically explore the impact of orbital exenteration and other management strategies. The analysis reveals that survival outcomes are closely linked to the timely initiation of antifungal therapy, the patient’s underlying conditions, and the extent of orbital involvement at the time of diagnosis. Our findings, in line with the literature, show that early-stage ROM can be treated successfully with less invasive methods, while advanced cases may require orbital exenteration. The need for exenteration should be evaluated on a case-by-case basis, with early detection and appropriate antifungal treatment being critical factors for survival. This study highlights the importance of early diagnosis and individualized treatment plans, emphasizing that while orbital exenteration may improve survival in severe cases, less invasive interventions should be considered for less advanced ROM. Further research and standardized guidelines are needed to refine treatment strategies.Keywords: Mucorales, orbital apex syndrome, ORBITAL exenteration, rhino-orbital mucormycosis, surgical debridement